2022
DOI: 10.3390/cancers14112720
|View full text |Cite
|
Sign up to set email alerts
|

Early Development of Ubiquitous Acanthocytosis and Extravascular Hemolysis in Lung Cancer Patients Receiving Alectinib

Abstract: Alectinib is a standard initial treatment for patients with advanced anaplastic lymphoma kinase (ALK) rearranged non-small-cell lung cancer (NSCLC). The current study analyzed a prospective cohort of 24 consecutive alectinib-treated patients and controls in order to comprehensively characterize longitudinal erythrocyte changes under treatment with ALK inhibitors. Upon starting alectinib, all examined patients developed reticulocytosis and abnormal erythrocyte morphology with anisocytosis and a predominance of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Upon multifocal progression in the left lung, chest wall, left breast, and left parotid gland 2 mo later, therapy was empirically switched to alectinib, which resulted in durable tumor shrinkage of >30%, corresponding to a partial response (PR) by RECIST v1.1. The treatment was generally well-tolerated without significant hemolysis, and a transient reduction of hemoglobin from 13.3 g/dL at baseline to 12.4 g/dL 1 wk later, gradually recovered within the next few weeks ( Kunz et al 2022 ). A second oligoprogression in the left breast 10 mo later was treated by surgical excision of the growing lesion, whose molecular workup revealed an ALK :p.V1180L mutation.…”
Section: Resultsmentioning
confidence: 99%
“…Upon multifocal progression in the left lung, chest wall, left breast, and left parotid gland 2 mo later, therapy was empirically switched to alectinib, which resulted in durable tumor shrinkage of >30%, corresponding to a partial response (PR) by RECIST v1.1. The treatment was generally well-tolerated without significant hemolysis, and a transient reduction of hemoglobin from 13.3 g/dL at baseline to 12.4 g/dL 1 wk later, gradually recovered within the next few weeks ( Kunz et al 2022 ). A second oligoprogression in the left breast 10 mo later was treated by surgical excision of the growing lesion, whose molecular workup revealed an ALK :p.V1180L mutation.…”
Section: Resultsmentioning
confidence: 99%
“…Alectinib is considered to invariably induce subclinical hemolysis in all patients with morphological changes such as acanthocytes or spherocytes of erythrocytes. 9 , 10 The US package insert of alectinib mentions potential for hemolytic anemia. Nevertheless, hemolytic anemia is underreported because many physicians are unaware of its existence.…”
Section: Discussionmentioning
confidence: 99%
“…In a similar vein to previous reports of alectinib-induced hemolytic anemia, the results of DAT were consistently negative. 8 , 9 , 12 , 13 The DAT demonstrates the presence of antibodies or complement on the surface of red blood cells. 16 The negative result for DAT suggested that the hemolysis observed was occurring via a nonimmune mechanism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies reveal that alectinib may include ubiquitous acanthocytosis and subclinical hemolysis though most patients do not suffer significant hemolytic anemia. 45 , 46 Abnormal erythrocyte morphology, increased reticulocytes, and decreased eosin-5-maleimide binding are helpful for the diagnosis of alectinib-induced hemolysis. 46 Withhold alectinib and initiate appropriate laboratory testing if hemolytic anemia is suspected.…”
Section: Management Of Alk-tki-associated Adrsmentioning
confidence: 99%